Re‐evaluation of fatty acids (E 570) as a food additive - Mortensen, Alicja (EFSA J, 2017)
The EFSA Panel on Food Additives and Nutrient Sources added to Food (ANS) provides a scientific opinion re‐evaluating the safety of fatty acids (E 570) when used as a food additive. The food additive includes caprylic‐ (C8), capric‐ (C10), lauric‐ (C12), myristic‐ (C14), palmitic‐ (C16), stearic‐ (C18) and oleic acid (C18:1), present alone or in combination. In 1991, the Scientific Committee on Food (SCF) established a group acceptable daily intake (ADI) ‘not specified’ for the fatty acids (myristic, stearic, palmitic and oleic acid). The fatty acids (E 570) are absorbed in the same way as the free fatty acids from the regular diet. They show low acute toxicity. The available studies on subchronic toxicity were limited but there was no evidence for toxic effects at doses up to 10% in the diet (equivalent to 9,000 mg lauric acid/kg body weight (bw) per day). The Panel considered that the fatty acids (E 570) did not raise a concern for genotoxicity. Data on chronic toxicity, reproductive toxicity and developmental toxicity were too limited to reach a conclusion on these endpoints. The Panel noted that the contribution of fatty acids (E 570) represented on average only 1% of the overall exposure to saturated fatty acids from all dietary sources (food additive and regular diet). Based on the approach described in the conceptual framework for the risk assessment of certain food additives re‐evaluated under Commission Regulation (EU) No 257/2010 and taking into account the considerations mentioned above, the Panel concluded that the food additive fatty acids (E 570) was of no safety concern at the reported uses and use levels.